Swollen liquid-crystalline lamellar phase based on extended solid-like sheets - Gabriel, J.C.P.; Camerel, F.; Lemaire, B.J.; Desvaux, H.; Davidson, P.; Batail, P. (Nature, 2001)
Ordering particles at the nanometre length scale is a challenging and active research area in materials science. Several approaches have so far been developed, ranging from the manipulation of individual particles(1,2) to the exploitation of self-assembly in colloids(3). Nanometre-scale ordering is well known to appear spontaneously when anisotropic organic moieties form liquid-crystalline phases; this behaviour is also observed for anisotropic mineral nanoparticles(4,5) resulting in the formation of nematic(4-7), smectic(8) and hexagonal(9,10) mesophases. Here we describe a lyotropic liquid-crystalline lamellar phase comprising an aqueous dispersion of planar solid-like sheets in which all the atoms involved in a layer are covalently bonded. The spacing of these phosphatoantimonate single layers can be increased 100-fold, resulting in one-dimensional structures whose periodicity can be tuned from 1.5 to 225 nanometres. These highly organized materials can be mechanically or magnetically aligned over large pH and temperature ranges, and this property can be used to measure residual dipolar couplings for the structure determination of biomolecules by liquid-state NMR. We also expect that our approach will result in the discovery of other classes of mineral lyotropic lamellar phases.